ATOMS: ALMA Three-millimeter Observations of Massive Star-forming regions – VIII. A search for hot cores by using C2H5CN, CH3OCHO, and CH3OH lines. Issue 3 (29th January 2022) - Qin, Sheng-Li; Liu, Tie; Liu, Xunchuan; Goldsmith, Paul F; Li, Di; Zhang, Qizhou; Liu, Hong-Li; Wu, Yuefang; Bronfman, Leonardo; Juvela, Mika; Lee, Chang Won; Garay, Guido; et al.
ABSTRACT: Hot cores characterized by rich lines of complex organic molecules are considered as ideal sites for investigating the physical and chemical environments of massive star formation. We present a search for hot cores by using typical nitrogen- and oxygen-bearing complex organic molecules (C2 H5 CN, CH3 OCHO, and CH3 OH), based on ALMA Three-millimeter Observations of Massive Star-forming regions (ATOMS). The angular resolutions and line sensitivities of the ALMA observations are better than 2 arcsec and 10 mJy beam −1, respectively. A total of 60 hot cores are identified with 45 being newly detected, in which the complex organic molecules have high gas temperatures (> 100 K) and hot cores have small source sizes (< 0.1 pc). So far, this is the largest sample of hot cores observed with similar angular resolution and spectral coverage. The observations have also shown nitrogen and oxygen differentiation in both line emission and gas distribution in 29 hot cores. Column densities of CH3 OH and CH3 OCHO increase as rotation temperatures rise. The column density of CH3 OCHO correlates tightly with that of CH3 OH. The pathways for production of different species are discussed. Based on the spatial position difference between hot cores and ultracompact H ii (UC H ii ) regions, we conclude that 24 hot cores are externally heated, while the other hot cores are internally heated. The observations presented here will potentially help establish a hot core template for studying massive star formation and astrochemistry.